2018
DOI: 10.1071/fp16242
|View full text |Cite
|
Sign up to set email alerts
|

Rapid changes in root HvPIP2;2 aquaporins abundance and ABA concentration are required to enhance root hydraulic conductivity and maintain leaf water potential in response to increased evaporative demand

Abstract: http://www.publish.csiro.au/nid/102.htm Functional Plant BiologyRapid changes in root HvPIP2;2 aquaporins abundance and ABA concentration are 1 required to enhance root hydraulic conductivity and maintain leaf water potential in 2 response to increased evaporative demand 3 4 Abstract. To address the involvement of abscisic acid (ABA) in regulating transpiration and root 14 hydraulic conductivity (Lp Root ) and their relative importance for maintaining leaf hydration, the 15 ABA-deficient barley mutant Az34 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 30 publications
2
26
1
Order By: Relevance
“…HvPIP2;5 , but not HvPIP2;2, was one of the three PIP genes which was reduced in gene expression by high Zn in the present study. Veselov et al () observed for barley plants, which were exposed to an increased vapour pressure deficit and transpirational demand, that an increase in root Lp was accompanied by a large increase in protein level of HvPIP2;2, while protein levels of HvPIP2;1 and HvPIP2;5 did not change. Katsuhara et al () studied changes in root Lp and gene transcript and protein level of HvPIP2;1 during day/night and concluded that HvPIP2;1 plays a key role in the diurnal root water uptake and plant transpiration response of barley.…”
Section: Discussionmentioning
confidence: 99%
“…HvPIP2;5 , but not HvPIP2;2, was one of the three PIP genes which was reduced in gene expression by high Zn in the present study. Veselov et al () observed for barley plants, which were exposed to an increased vapour pressure deficit and transpirational demand, that an increase in root Lp was accompanied by a large increase in protein level of HvPIP2;2, while protein levels of HvPIP2;1 and HvPIP2;5 did not change. Katsuhara et al () studied changes in root Lp and gene transcript and protein level of HvPIP2;1 during day/night and concluded that HvPIP2;1 plays a key role in the diurnal root water uptake and plant transpiration response of barley.…”
Section: Discussionmentioning
confidence: 99%
“…Five millimeter root segments were fixed for 12 h in a solution of 4% N-(3-Dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (Merck, Darmstadt, Germany) prepared in 0.1 M phosphate buffer (pH 7.2-7.4). Carbodiimide not only fixes proteins, but also conjugates ABA with tissue proteins [16,17]. Then, root tissues were placed in a mixture of 4% paraformaldehyde (Riedel de Haen, Seelze, Germany) and 0.1% glutaraldehyde (Sigma) for 12 h. After fixation, plant tissues were washed for 1 h in phosphate buffer and successively kept for 30 min in ethanol dilutions for their dehydration.…”
Section: Preparation Of Tissue Sectionsmentioning
confidence: 99%
“…Such possibility is supported by findings of Kudoyarova et al . (2011) on durum wheat and Veselov et al . (2018) on barley, indicating that high VPD triggers leaf ABA export to the root to regulate root hydraulic conductivity, as a way to maintaining leaf hydration as increases.…”
Section: Introductionmentioning
confidence: 93%
“…Currently, there is evidence supporting the idea that whole-plant TR response to VPD involves an interaction between ‘local’ (i.e., leaf-based) and ‘non-local’ (root-based) mechanisms mobilizing long-distance hydraulic signals that involve a combination of root anatomical traits and a dynamic control over radial water flow mediated by aquaporins (Vandeleur et al ., 2014; Vadez, 2014; Maurel et al ., 2016; Sivasakthi et al ., 2017). However, other investigations point to a role played by a shoot-to-root hormonal signal, namely abscisic acid (ABA) in coordinating TR with root hydraulic conductivity in response to increasing VPD (Kudoyarova et al ., 2011; Veselov et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%